Anomaly-induced dynamical refringence in strong-field QED - Müller, Niklas; Hebenstreit, Florian; Berges, Jürgen (Arxiv, 2016)
We investigate the impact of the Adler-Bell-Jackiw anomaly on the nonequilibrium evolution of strong-field quantum electrodynamics (QED) using real-time lattice gauge theory techniques. For field strengths exceeding the Schwinger limit for pair production, we encounter a highly absorptive medium with anomaly-induced dynamical refractive properties. In contrast to earlier expectations based on equilibrium properties, where net anomalous effects vanish because of the trivial vacuum structure, we find that out-of-equilibrium conditions can have dramatic consequences for the presence of quantum currents with distinctive macroscopic signatures. We observe an intriguing tracking behavior, where the system spends longest times near collinear field configurations with maximum anomalous current. Apart from the potential relevance of our findings for future laser experiments, similar phenomena related to the chiral magnetic effect are expected to play an important role for strong QED fields during initial stages of heavy-ion collision experiments.